AMIR TIMUR AND TIMURID'S PERIOD - Zebiniso Gavharbekova Nodirbek kizi (TADQIQOTLAR.UZ, 2024)
Abstract: This abstract explores the enduring legacy of Amir Timur and the Timurid period, focusing on their impact on Central Asia and beyond during the 14th and 15th centuries. Amir Timur, also known as Tamerlane, rose from humble beginnings to become a formidable conqueror whose military campaigns reshaped the geopolitical landscape of Eurasia. The Timurid Empire, established by Timur, became a hub of cultural exchange and artistic innovation, exemplified by the architectural marvels of Samarkand and the intellectual achievements of Timurid scholars.